The Influence of Social Media Marketing and Price on Purchase Decisions Through Brand Image as An Intervening Variable (Samsung Smartphone) - Mutiara Firda Rosdiana; Yulia Nur Hasanah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Currently, Indonesia has several companies that have marketed their goods or services through social media. One of the companies that use social media to inform their products is the Samsung company that uses Instagram accounts to inform their newest products. Samsung is the most popular smartphone manufacturer in Asia and the world. But there are many other competitors who are trying to shift Samsung's power. The method used in this research is using quantitative research methods with descriptive and causal research types. The population used in this study, namely the Indonesian people who use Samsung smartphones with a sample of 120 respondents. Sampling used in this study, namely the purposive sampling method. The data analysis technique used the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results of the descriptive analysis show that Social Media Marketing, Price and Purchase Decisions are in good category while Brand Image is in very good category. From the results of the hypothesis that Social media marketing has an effect on Brand Image, Price has an effect on Brand Image, Social media marketing has no effect on Purchase Decisions, Price has an effect on Purchase Decisions, Brand Image has an effect on Purchase Decisions, Social media marketing has an effect on Purchase Decisions through Brand Image, Price has an effect on Purchase Decision through Brand Image, Social media marketing and Price has an effect on Purchase Decision through Brand Image.